2021
DOI: 10.1101/2021.09.24.461751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endotaxis: A neuromorphic algorithm for mapping, goal-learning, navigation, and patrolling

Abstract: An animal entering a new environment typically faces three challenges: explore the space for resources, memorize their locations, and navigate towards those targets as needed. Experimental work on exploration, mapping, and navigation has mostly focused on simple environments - such as an open arena, a pond [1], or a desert [2] - and much has been learned about neural signals in diverse brain areas under these conditions [3,4]. However, many natural environments are highly constrained, such as a system of burro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
(214 reference statements)
0
10
0
Order By: Relevance
“…Typically, for purposes of fitting neural data or for RL simulations, γ will take on values as high as 0.9 [18, 49]. However, previous work that used RNN models reported that recurrent dynamics become unstable if the gain γ exceeds a critical value [42, 45]. This could be problematic as we show analytically that the RNN-S update rule is effective only when the network dynamics are stable and do not have non-normal amplification (Supplementary Notes 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Typically, for purposes of fitting neural data or for RL simulations, γ will take on values as high as 0.9 [18, 49]. However, previous work that used RNN models reported that recurrent dynamics become unstable if the gain γ exceeds a critical value [42, 45]. This could be problematic as we show analytically that the RNN-S update rule is effective only when the network dynamics are stable and do not have non-normal amplification (Supplementary Notes 2).…”
Section: Resultsmentioning
confidence: 99%
“…Because equivalence is only reached in the asymptotic limit of learning (i.e., ∆J → 0), our RNN-S model learns the SR slowly. In contrast, animals are thought to be able to learn 123 the structure of an environment quickly [45], and neural representations in an environment can also develop quickly [46,47,48]. To remedy this, we introduce a dynamic learning rate that allows for faster normalization of the synaptic weight matrix, similar to the formula for calculating a moving average (Supplementary Notes 4).…”
Section: Evaluating Sr Learning By Biologically Plausible Learning Rulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, expressing excessive emphasis on those goals is a sign of psychological disorders [16,17]. Further, setting a reward function by design as the goal of intelligent agents is more often than not arbitrary [14,18,19], leading to the recurrent problem faced by theories of reward maximization of defining what rewards are [20][21][22][23][24]. In some cases, like in artificial games, rewards can be unambiguously defined, such as number of collected points or wins [25].…”
Section: Introductionmentioning
confidence: 99%